Prospecção genética de bactérias isoladas de nódulos de mucuna (Mucuna aterrima) do cerrado goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Mucuna is a legume used as green manure, during intercrop period, in farming system. The plant association with microrganisms, which are able to perform biological nitrogen fixation (BNF), is an alternative and advantageous way of promoting growth as well as to improve soil quality. The aim of this study is to characterize, by molecular methods, the genomic structure of 24 bacteria which were isolated from root nodules of mucuna (Mucuna aterrima). Mucuna plants were grown in soil colected from 3 different cities in Goias state: Rio Verde, Poranguatú and Santo Antônio de Goiás. Molecular methods were based on genome separation using pulsed field gel eletrocphoresis (PFGE) technique, and by using amplification of conserved and non-conserved regions of genome throught polymerase chain reaction (PCR) technique. It was also performed the sequencing of the 16S rRNA region, and its restriction by using restriction endonuclease Haelll (ARDRA). The assays results obtained were treated by using similarity analysis based on Jaccard’s coefficient and UPGMA algorithm to construct a similarity dendrogram, in order to estimate phylogenetic relation of the bacterial isolates. The sequencingwere compared to the sequences of endophytic bacteria from NCBI database. PFGE analysis showed a circular genetic material with high molecular weight and replicon of 1,2 Mb for most of isolates. IRS 16-23S and REP regions have been considered high discriminatory power intraspecies. The study of the housekeeping (glnll e atpD) regions has shown to be unsuitable for MLSA (Multilocus Sequence Analysis) test, however it can be used in phylogentic polymorphism studies as well in melA gene. The nifH gene was presented in 6 isolates of mucuna. Whereas the nodC gene was not found in any of the isolates. The 16S rRNA region presented fragments of 1,5kb for all the isolates and its restriction to Haelll enzyme presented a better clustering for phylogenetic separation. The sequencing database were compared to NCBI database sequences to obtain bacteria identification. There were identified 11 isolates with similarity over 91% considering genus Enterobacter, Bacillus, and Stenotrophomonas. These genotypic features aim to aid understanding the relation between bacteria which were isolated from nodules and host plants, as well as to investigate the dynamic of the genomic structure of these prokaryotes, and the diversity of bacteria associated with mucuna. The study can also help in the strategy of selecting groups of bacteria to be used as inoculants to mucuna culture in the ‘Cerrado goiano’.
Keywords: Genoma; Mucuna; Bactérias endofíticas; Inoculantes e simbiose; Genome; Mucuna; Endophytic bacteria and symbiosis; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA